Sosialisasi mitigasi bencana: aman dari bencana tanah longsor dan luapan air (AMERTA) - Pratama, Reza Hardian; Purwoko, Eko; Husna, Nurul; Julian, Aqlifa Hanif (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Indonesia’s complex topography, geology, and climate make hilly areas such as Karang Rejo Village in Ulubelu Subdistrict, Tanggamus Regency highly vulnerable to landslides and flash floods. Steep slopes, unstable soil conditions, unsustainable land use practices, and unmanaged household waste accumulation contribute to disaster risk and environmental pollution. Open burning of waste further exacerbates health risks due to the emission of toxic substances and fine particulates. Limited waste processing facilities compel residents to locate disposal sites on the village outskirts, increasing both financial burdens and environmental impacts. Purpose: Improving the capacity of the Karang Rejo Village community in mitigating landslide and flood risks through integrated disaster education, as well as introducing and testing the effectiveness of environmentally friendly waste incineration tools. Method: The community service activity themed